2010
DOI: 10.1111/j.1600-6143.2009.02868.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with Nonglycosaminoglycan‐Binding Mutant CCL7: A Novel Strategy to Limit Allograft Inflammation

Abstract: Chemokines are immobilized by binding to glycosaminoglycans (GAGs). A non-GAG-binding mutant CCL7 (mtCCL7) was developed that retained its affinity for chemokine receptors. This mtCCL7 induced leukocyte chemotaxis in diffusion gradients but did not stimulate trans-endothelial migration (p < 0.01). Unlike wild-type CCL7, mtCCL7 persisted in the circulation of BALB/c mice for more than 6 h and prevented leukocyte infiltration of skin isografts (p < 0.05). Treatment with mtCCL7 marginally increased the survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…It was found that unlike WT-CCL2, the NO 2 -CCL2 was not capable of inducing transendothelial leukocyte migration in vitro . A similar failure of cell migration has been reported previously for leukocyte transmigration assays performed using non-GAG binding chemokines152930.…”
Section: Discussionsupporting
confidence: 85%
“…It was found that unlike WT-CCL2, the NO 2 -CCL2 was not capable of inducing transendothelial leukocyte migration in vitro . A similar failure of cell migration has been reported previously for leukocyte transmigration assays performed using non-GAG binding chemokines152930.…”
Section: Discussionsupporting
confidence: 85%
“…That these interactions are important has been convincingly demonstrated by several studies which showed that chemokine mutants devoid of their ability to oligomerize or interact with GAGS are functionally deficient in vivo. 22,45,96 …”
Section: Chemokine Structurementioning
confidence: 99%
“…This is exemplified by a mutation of proline 8 into alanine in CCL2, which resulted in an obligate monomeric form that retained in vitro activity towards CCR2 but nevertheless acted as an antagonist in vivo , possibly by displacing endogenous CCL2 from GAGs on the vessel wall (Handel et al, 2008). Likewise, mutation of the GAG‐binding sites in CCL5, CCL7 and CXCL12 yielded chemokine mutants that were competent in receptor activation in vitro but possessed anti‐inflammatory dominant‐negative properties in animal models of inflammation, including atherosclerosis (Ali et al, 2010; Braunersreuther et al, 2008; O'Boyle et al, 2009). It is intriguing how chemokine mutants with reduced oligomerization or binding to GAGs might nevertheless act as inhibitors for their wild‐type counterparts.…”
Section: Novel Classes Of Chemokine Blockersmentioning
confidence: 99%